Industrial Pipe-Rack Health Monitoring System Based on Reliable-Secure Wireless Sensor Network - Jong-Han Lee; Ji-Eun Jung; Nam-Gyu Kim; Byung-Hun Song (International Journal of Distributed Sensor Networks)
Energy and power industrial plants need to improve the health monitoring systems of their facilities, particularly high-risk facilities. This need has created a demand for wireless sensor networks (WSNs). However, for the application of WSN technology in large-scale industrial plants, issues of reliability and security should be fully addressed, and an industrial sensor network standard that mitigatesthe problem of compatibilitywith legacy equipment and systems should be established. To fulfill these requirements, this study proposes a health monitoring system of the pipe-rack structure using ISA100.11a standard. We constructed the system, which consists of field nodes, a network gateway, and a control server, and tested its operation at a large-scale petrochemical plant. The data obtained from WSN-based sensors show that the proposed system can constantly monitor and evaluate the condition of the pipe-rack structure and provide more efficient risk management.